Homocysteine Levels in Severe OSA Patients Before and After TORS‐OSA Surgery. (29th January 2023) - Chiu, Li‐Wen; Lin, Chung‐Wei; Lin, Pei‐Wen; Chai, Han‐Tan; Chang, Chun‐Tuan; Friedman, Michael; Salapatas, Anna M.; Lin, Hsin‐Ching
Abstract: Objective: The increased risk of cardiovascular diseases owing to a high level of serum homocysteine has been widely reported. Literature has demonstrated that patients with obstructive sleep apnea/hypopnea syndrome (OSA) had a higher homocysteine level than control group. This study aimed to investigate the alteration of serum homocysteine levels in severe OSA patients receiving transoral robotic surgery (TORS). Study Design: Retrospective chart review. Setting: Tertiary academic medical center. Methods: Data of polysomnography (PSG) and serum homocysteine levels before and at least 3 months after the surgery were collected and analyzed via paired t tests. A subgroup analysis based on the preoperative homocysteine level (≥15 mcmol/L, as hyperhomocysteinemia group) was conducted to compare the intergroup differences of homocysteine decrease. Pearson's correlation was used to survey the relationships between the changes of major PSG parameters and the levels of homocysteine decrease at baseline and after TORS‐OSA surgery. Results: Two hundred sixty‐one patients with severe OSA were enrolled. There were significant improvements in major PSG parameters after TORS‐OSA surgery. Homocysteine levels significantly decreased from 12.1 ± 3.9 to 11.4 ± 3.7 mcmol/L (difference = −0.7 ± 2.8 mcmol/L, p  = .001) postoperatively, which was shown in the hyperhomocysteinemia group (difference = −2.9 ± 4.7 mcmol/L, p  = .007) to a greater extent. Pearson's correlation revealed that ΔODI (oxygen desaturation index/h) was the predominant estimate with a positive association with Δhomocysteine ( r  = 0.525, p  = .012). Conclusion: TORS‐OSA surgery could decrease homocysteine levels in OSA patients. The effects were more relevant in severe OSA patients with abnormal preoperative homocysteine levels.